Myxosarcoma in a dwarf hamster (Phodopus sungorus) - Mazlan, Mazlina; Selvarajah, Gayathri Thevi; Byron Chong, Y L; Law, H L (2018)
A 1.5 years old female Russian dwarf hamster (Phodopus sungorus) was presented with a large mass at right caudal ventral abdomen. Lumpectomy was performed to remove the growth mass and subjected to histopathological examination. The encapsulated mass was 3 cm x 4 cm, grossly solitary, non-ulcerated and pinkish in colour with presence of mucous-like substances on cut surface. Routine histopathology using hematoxylin and eosin staining revealed presence of pleomorphic, loosely arranged stellate to spindle shaped cells, angiogenesis, abundant neutrophils, necrotized tissues and high number of mitotic figures. Tumour tissue was positive for Alcian blue (pH 2.5) stain but negative for Periodic acid-Schiff (PAS) staining which suggests presence of acid mucin which confirmed the diagnosis of myxosarcoma. One month post-surgery, the hamster showed absence for local recurrence of the tumour, but it died a few months later due to unrelated cause.